Lā‘ei Sāmoa: From public servants' uniform to national attire? - Kuramitsu, Minako (Waka Kuaka, 2016)
This article considers reproduction of 'Sāmoanness' through the process by which Lā'ei Sāmoa, a simple dress code for public servants, came to be viewed as the national attire. The initial objections at the inauguration of Lā'ei Sāmoa did not persist, because of the impossibility of establishing an acceptable historical and cultural authenticity of Sāmoan national attire. Over a three-year period, Lā'ei Sāmoa also brought fortuitous economic benefits to the Sāmoan clothing industry and diversified the Sāmoan culture of clothing. Considering how the Sāmoan Government took the initiative on the introduction of Lā'ei Sāmoa, it could be understood as the silent struggle of the nation to establish its distinctive 'Sāmoanness'.